Scalable detection of technically challenging variants through modified next‐generation sequencing. Issue 12 (17th October 2022) - Rojahn, Susan; Hambuch, Tina; Adrian, Jessika; Gafni, Erik; Gileta, Alex; Hatchell, Hannah; Johnson, Britt; Kallman, Ben; Karfilis, Kate; Kautzer, Curtis; Kennemer, Michael; Kirk, Lloyd; et al.
Abstract: Background: Some clinically important genetic variants are not easily evaluated with next‐generation sequencing (NGS) methods due to technical challenges arising from high‐ similarity copies (e.g., PMS2, SMN1/SMN2, GBA1, HBA1/HBA2, CYP21A2 ), repetitive short sequences (e.g., ARX polyalanine repeats, FMR1 AGG interruptions in CGG repeats, CFTR poly‐T/TG repeats), and other complexities (e.g., MSH2 Boland inversions). Methods: We customized our NGS processes to detect the technically challenging variants mentioned above with adaptations including target enrichment and bioinformatic masking of similar sequences. Adaptations were validated with samples of known genotypes. Results: Our adaptations provided high‐sensitivity and high‐specificity detection for most of the variants and provided a high‐sensitivity primary assay to be followed with orthogonal disambiguation for the others. The sensitivity of the NGS adaptations was 100% for all of the technically challenging variants. Specificity was 100% for those in PMS2, GBA1, SMN1 / SMN2, and HBA1/HBA2, and for the MSH2 Boland inversion; 97.8%–100% for CYP21A2 variants; and 85.7% for ARX polyalanine repeats. Conclusions: NGS assays can detect technically challenging variants when chemistries and bioinformatics are jointly refined. The adaptations described support a scalable, cost‐effective path to identifying all clinically relevant variants within a single sample. Abstract : Some clinically important genes and variants are not easily detected with standard next‐generation sequencing (NGS) methods due to technical challenges arising from high‐similarity copies, repetitive short sequences, and other complexities. When the chemistries and bioinformatics of NGS are jointly refined, even technically challenging genes and variants can be evaluated, including the Gaucher disease‐associated GBA, which has a high‐similarity pseudogene.